Algoritmos sensibles (2020)
Paint or paintings can change, transform, adapt or even mutate. One way of adaptation is to appropriate or embrace digital technology, because the multiple software gives us the opportunity to paint without materials, this type of doing paintings limits the creative processes. Also, it leaves out the idea of analyzing the materials of a painting and that becomes a limitation in texture and creativity. Paintings or paint is a material the we can touch, feel, analyze, we have control of where or how we want it, but also it has an extra element where she can be influenced by random factors. Paint can make us feel closer to the real world and separates us from the neat and superficial, because we are expose to this factors everyday in our screens. This project aims to use and blend the digital with the analogous, digital not only by using new materials but also by embracing new languages that we can find in our live...